Faktor-Faktor yang Mempengaruhi Nilai Perusahaan pada Perusahaan yang Terdaftar di Bursa Efek Malaysia dan Bursa Efek Indonesia - Sri Hermuningsih; Dewi Kusuma Wardani (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2009)
The objective of this study was proving the influences of insider ownership, debt policy and dividend policy to firm value at companies listed in Malaysia Stock Exchange and Indonesia Stock Exchange during 2003 to 2008. This study used multistage regression to reach the objective. The results indicate that in Malaysia, insider ownership and debt policy have an effect to dividend policy but have not a significant effect to firm value and in Indonesia, insider ownership and debt policy have not an effect to dividend policy and dividen policy also not have an effect to company value. Beside that the Malaysian and Indonesia investors do not use a dividend policy as a positif signal because many firms give dividend although they have not profit. Keywords: insider ownership, debt policy, dividend policy, firm value